Molecular interaction studies of green tea catechins as multitarget drug candidates for the treatment of Parkinson's disease: computational and structural insights. (2nd October 2015) - Azam, Faizul; Mohamed, Najah; Alhussen, Fatma
Abstract: Green tea catechins have extensively been studied for their imminent role in reducing the risk of various neurodegenerative diseases such as Parkinson's disease (PD). Understanding the molecular interaction of these compounds with various anti-Parkinsonian drug targets is of interest. The present study is intended to explore binding modes of catechins with molecular targets having potential role in PD. Lamarckian genetic algorithm methodology was adopted for molecular docking simulations employing AutoDock 4.2 program. Toxicity potential and molecular properties responsible for good pharmacokinetic profile were calculated by Osiris property explorer and Molinspiration online toolkit, respectively. A strong correlation coefficient ( r 2 = 0.893) was obtained between experimentally reported and docking predicted activities of native co-crystallized ligands of the 18 target receptors used in current study. Analysis of docked conformations revealed monoamine oxidase-B as most promising, while N-methyl-D-aspartate receptor was recognized as the least favorable target for catechins. Benzopyran skeleton with a phenyl group substituted at the 2-position and a hydroxyl (or ester) function at the 3-position has been identified as common structural requirements at majority of the targets. The present findings suggest that epigallocatechin gallate is the most promising lead to be developed as multitarget drug for the design and development of novel anti-Parkinsonian agents.